Parameterized Model for Virtual Human Deformation (Journal of Fiber Bioengineering and Informatics, 2018)
With the development of the theory of virtual reality, three-dimensional virtual human is being appliedin clothing engineering design. Parameterized model for virtual human body hence becomes more andmore important. In this paper, a parameterized model for virtual human body was reported. In thismodel, the virtual human body was partitioned into several parts (head, right arm, left arm, trunk, rightleg, and left leg). Based on the partitioned human model, the proportional characteristics of the humanbody were used to calculate the offset of the vertices to implement the deformation on specific part ofthe body. The interpolation method was used to smoothen the deformed surfaces. The experimentalresults show that this method had good deformation effect.
Keywords: Virtual Human; Deformation; Parameterized